Inoculation with Jeotgalicoccus sp. improves nutritional quality and biological value of Eruca sativa by enhancing amino acid and phenolic metabolism and increasing mineral uptake, unsaturated fatty acids, vitamins, and antioxidants - Hassan, Abdelrahim H. A.; Maridueña-Zavala, Maria Gabriela; Alsherif, Emad A.; Aloufi, Abeer S.; Korany, Shereen Magdy; Aldilami, Mohammad; Bouqellah, Nahla A.; Reyad, Ahmed M.; AbdElgawad, Hamada (Frontiers in Plant Science, 2024)
Plant growth-promoting bacteria (PGPB) are considered a promising tool for triggering the synthesis of bioactive compounds in plants and to produce healthy foods. This study aimed to demonstrate the impact of PGPB on the growth, accumulation of primary and secondary metabolites, biological activities, and nutritional qualities of Eruca sativa (arugula), a key leafy vegetable worldwide. To this end, Jeotgalicoccus sp. (JW0823), was isolated and identified by using partial 16S rDNA based identification and phylogenetic analysis. The findings revealed that JW0823 significantly boosted plant biomass production by about 45% (P<0.05) and enhanced pigment content by 47.5% to 83.8%. JW0823-treated plants remarkable improvements in their proximate composition and vitamin contents, with vitamin E level increasing by 161.5%. JW0823 induced the accumulation of bioactive metabolites including antioxidants, vitamins, unsaturated fatty acids, and essential amino acids, thereby improving the nutritional qualities of treated plants.An increase in the amounts of amino acids was recorded, with isoleucine showing the highest increase of 270.2%. This was accompanied by increased activity of the key enzymes involved in amino acid biosynthesis, including glutamine synthase, dihydrodipicolinate synthase, cystathionine γ-synthase, and phenylalanine ammonia-lyase enzymes. Consequently, the total antioxidant and antidiabetic activities of the inoculated plants were enhanced. Additionally, JW0823 improved antimicrobial activity against several pathogenic microorganisms. Overall, the JW0823 treatment is a highly promising method for enhancing the health-promoting properties and biological characteristics of E. sativa, making it a valuable tool for improving the quality of this important leafy vegetable.